Nostalgic collections. Issue 2 (4th March 2017) - Cross, Gary
ABSTRACT: Nostalgia has been transformed by the consumer market. With the emergence of ephemeral novelty goods – popular music, TV serials, kitsch, automobiles, and especially playthings – nostalgia has become less about identification with past communities, ideologies, or regimes than associated with fast-changing consumer goods, especially those encountered in childhood and youth. Reappropriating those goods later in life in nostalgic collecting has become a big business, producing narrow cohorts of consumers sharing common consumer memories. I explore this phenomenon through the history of collecting toys, dolls, and Disney collectibles in the USA.